Análise de artigos na interface entre História da Química e ensino (1994- 2014): alguns aspectos historiográficos - Trindade, Ana Paula Pires (2015)
This work has been developed as part of the "History of science and education: interdisciplinary approaches in Higher Education (diagnosis, continuous and specialist training for teachers)", Supported by the Centre for Education Program - OBEDUC (CAPES / INEP process 23038.002603 / 2013 -47. The main purpose of this study is collecting articles regarding the interface History of Science and Education, published in the education periodics, as well as analyzing the historiographical perspectives, both in quantity and quality, concerning the selected articles. This study intends to show the historiographical perspective on the texts in the History of Chemistry published in the last twenty years. The leading axis of this analysis is vision of History of Science as an specific interdisciplinary field, in which studies are developed in three different analysis spheres (historiographical, epistemological and contextual), emphasizing that this study s approach is historiographical. The influence of CESIMA will also be studied in this dissertation